Implicações da governança pública para a gestão da extensão universitária na Universidade Estadual da Paraíba - Belo, Layse Ingrid Batista (2022)
This research presents the theory, foundations, contradictions and implications that public governance brings to the management of universities. Public governance is present in the management of universities, relying on political and financial relations, as it is the result of the “commodification” of the public sector that appeared in the Brazilian scenario from the 90s with the Reform of the Brazilian State. Brazilian universities are supported by the tripod - teaching, research and extension, and in this research the importance of university extension for state universities will be presented. As a scenario, the research presents the environment of budget cuts that challenge the management of UEPB in extension activities. It is intended to present the implications that public governance causes to the management of the university extension of UEPB in the face of the challenges imposed by the policy of budget cuts of the state government of Paraíba applied to the institution. To carry out this analysis, it was necessary to present data on university extension at UEPB from 2010 to 2020 and apply a questionnaire to the team of the Dean of Extension of UEPB to verify if governance mechanisms are used in the sector. The research has a quantitative-qualitative approach, regarding the objectives it is exploratory and descriptive, regarding the type it is a Case Study, the sources of information were bibliographic and documentary, the analysis of the data was carried out through Descriptive Statistics Technique. In order to know the challenges that the institution had in the face of the crisis scenario established with the State, it was necessary to collect data through the transcription of the speeches of the managers of the administrative prorectories, available on the UEPB Transparency Portal and on the YouTube channel called “RedeUEPB”. Through the analysis, it was observed that: first, based on institutional data, university extension did not obtain a relevant variation in the results of the eight analyzed extension activities. Second, the institutional scenario related to budget cuts revealed that during the research period, the UEPB went through a major financial and political crisis established between the state and the institution, which resulted in a difficult management and instructed by the market to use public governance mechanisms. (Leadership, Strategy and Control). And third, the PROEX team analyzed the governance mechanisms and showed that everyone understands the use of these mechanisms in the management of the sector and the institution. As a result, it is inferred that public governance implied changes in the institution's management routine in the analyzed period, but these changes did not lead to important solutions to provide a comfortable financial and political scenario for the management of the institution nor for the management of university extension.